El cultivo de la Dalia (Dahlia spp) - Lopez Huerta, M. de L.=700 1 Alfaro Maya, C.
(ES, En)
Ilus., 19 ref.
Keywords: DAHLIA; CULTIVO; PROPAGACION VEGETATIVA; TUBERCULO; ESQUEJADO; MEXICO; REVISTA CHAPINGO